Evaluating Serum Amyloid A as a Biomarker in Preeclampsia - Montadhar K. Sultan; Moaed E. Al-Gazally; Bushra J. Al-Rubayae (International Journal of Biomedicine)
Background: Preeclampsia (PE) is the major cause of perinatal morbidity and mortality. The causes of the condition can be ascribed to excessive maternal systemic inflammatory response to pregnancy. Emerging evidence indicates that serum amyloid A (SAA), the acute phase response protein, may be a damage-associated molecular pattern molecule in pregnancy. This study aimed to evaluate serum amyloid A as a biomarker in preeclampsia. Methods and Results: This case-control study was conducted at Babylon Teaching Hospital for Maternity and Children from January 23, 2024, to June 13, 2024. The study involved 65 patients diagnosed with PE during their third trimester and 65 healthy expectant mothers. Preeclampsia was diagnosed according to the criteria of the American College of Obstetricians and Gynecologists (ACOG, 2020). Patients provided midstream urine samples for protein level estimation using dipstick tests. After a rest, blood pressure was measured three times, and the final recorded reading was the average of the two lowest readings from those three measurements. The sandwich-ELISA method was used to estimate Human SAA levels. The median SAP in the PE group was 38.48 μg/mL versus 30.74 μg/mL in the control group (P<0.001). We found significantly higher SAA levels in PE patients with stage 2 hypertension than in PE patients with elevated blood pressure or stage 1 hypertension (P=0.036). Conclusion: SAA is a promising biomarker for predicting the progression of preeclampsia. Further study of SAA during pregnancy may explain how inflammation is initiated in gestational tissues in normal and abnormal pregnancies.